THE RELATIONSHIPS BETWEEN MASTICATION AND BRAIN FUNCTIONS: A REVIEW - Andrei KOZMA; Doriana AGOP-FORNA; Norina FORNA (Romanian Dental Association for Education, 2019)
The active mastication has not only role in food intake and digestion, but also in the maintaining and promotion of the cognitive functions. It was demonstrated the increase of the blood supply in neuronal areas during mastication due to the stimulation of dental baroreceptors, alveolar baroreceptors and masticatory muscles during. Chewing was associated with greater alertness, more positive mood, faster reaction times, improved focus as well as with the improvement of the learning ability. On the other part, epidemiologic studies found that elderly individuals with high number of absent teeth are more likely to develop cognitive dysfunction, and neurodegenerative diseases like Alzheimer and dementia.